2020
DOI: 10.3389/fcimb.2020.600112
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum DHFR and DHPS Mutations Are Associated With HIV-1 Co-Infection and a Novel DHPS Mutation I504T Is Identified in Western Kenya

Abstract: Antifolate resistance is significant in Kenya and presumed to result from extensive use and cross-resistance between antifolate antimalarials and antibiotics, including cotrimoxazole/Bactrim used for HIV-1 chemotherapy. However, little is known about antifolate-resistant malaria in the context of newly diagnosed HIV-1 co-infection prior to administration of HIV-1 chemotherapy. Blood samples from a cross-sectional study of asymptomatic adult Kenyans enrolled during voluntary HIV testing were analyzed by PCR for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…Contrary to parasitemia data above, asymptomatic individuals infected with HIV-1 have been shown to have a significantly higher risk of being gametocyte positive, and with a higher relative gametocyte density, compared to HIV-1-negative individuals (Stiffler et al, 2020). Further, HIV-1 co-infection is associated with significant differences in P. falciparum dhfr and dhps haplotypes in the same patient population, suggesting that HIV-1 co-infection could impact the spread of drug resistance (Torrevillas et al, 2020). These observations are concerning in the context of transmission reduction, especially considering the high prevalence of asymptomatics in varying endemnicities (Alves et al, 2005;Bousema et al, 2014;Sattabongkot et al, 2018;Tadesse et al, 2018) and areas with seasonal transmission.…”
Section: Population Of Special Interest: Asymptomatic Individualscontrasting
confidence: 56%
“…Contrary to parasitemia data above, asymptomatic individuals infected with HIV-1 have been shown to have a significantly higher risk of being gametocyte positive, and with a higher relative gametocyte density, compared to HIV-1-negative individuals (Stiffler et al, 2020). Further, HIV-1 co-infection is associated with significant differences in P. falciparum dhfr and dhps haplotypes in the same patient population, suggesting that HIV-1 co-infection could impact the spread of drug resistance (Torrevillas et al, 2020). These observations are concerning in the context of transmission reduction, especially considering the high prevalence of asymptomatics in varying endemnicities (Alves et al, 2005;Bousema et al, 2014;Sattabongkot et al, 2018;Tadesse et al, 2018) and areas with seasonal transmission.…”
Section: Population Of Special Interest: Asymptomatic Individualscontrasting
confidence: 56%
“…34 In other studies of our volunteers published elsewhere, we observed that HIV-1-infected individuals had an increased risk of carrying gametocytes relative to HIV-1-uninfected individuals. 35 Furthermore, we observed that P. falciparum mutation haplotypes for the folate pathway genes dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) were significantly associated with volunteer HIV-1 status, 36 observations that collectively suggest that asymptomatic coinfected reservoirs in Western Kenya could be fueling transmission of drug-resistant parasites.…”
Section: Discussionmentioning
confidence: 94%
“…), 1,116 had adequate remaining DBS for gametocyte transcript analysis by qPCR. Samples collected for this study were also analyzed for the prevalence of antifolate resistance makers in the context of HIV-1 co-infection (Torrevillas et al, 2020).…”
Section: Sample Collection In Kombewa Kenyamentioning
confidence: 99%